2013
DOI: 10.1002/iub.1141
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone inhibits growth of K562/adriamycin cells by downregulating Bcr/Abl and P‐glycoprotein expression

Abstract: Alantolactone, a sesquiterpene lactone containing an a-methylene-c-lactone group, is the active component of Inula helenium (Compositae), a traditional Chinese medicinal herb. It has been reported that alantolactone has the capacity to inhibit tumor cell growth through induction of apoptosis. The purpose of this study was to assess the effects of alantolactone in the adriamycin (ADR)-resistant human erythroleukemia cell line K562/ADR, and provide evidence that it might function as a potent therapeutic agent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Bcr-Abl is frequently the causative agent in CML and is known to be associated with drug resistance (1). It has been reported that SAHA enhances sensitivity to imatinib in CML cells by decreasing the level of the Bcr-Abl protein and that this effect is associated with apoptosis (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcr-Abl is frequently the causative agent in CML and is known to be associated with drug resistance (1). It has been reported that SAHA enhances sensitivity to imatinib in CML cells by decreasing the level of the Bcr-Abl protein and that this effect is associated with apoptosis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic myeloid leukemia (CML) is a hematopoietic stem cell disorder, characterized by the expression and abnormal tyrosine kinase activity of the Bcr-Abl protein (1). The current recommended first line therapy for patients with newly diagnosed CML, is imatinib.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been documented that alantolactone significantly increased the expression of p53 in HepG2 cells (49,50) with concomitant increase of its downstream target genes, mainly cyclin-dependent kinase inhibitor p21 in adriamycin-resistant human erythroleukemia cell line K562/ADR (51). Alantolactone induces p53-independent apoptosis in prostate cancer PC-3 cells (52).…”
Section: P53 and Its Family Members Pathwaymentioning
confidence: 95%
“…Therefore, to arrest cancerous cell proliferation, regulation of apoptosis and its signaling pathways play a critical role (8,147,148). This behavior may lead to cellcycle arrest and upregulation of proapoptotic-related proteins expression (49)(50)(51). In addition, it also documented that the selected natural compounds induced cell-cycle arrest either G 2 -M, or S or G 0 -G 1 phase.…”
Section: Targeting Cancer Cells By Cell-cycle-mediated Apoptosis Pathwaymentioning
confidence: 96%
See 1 more Smart Citation